O desafio do contraditório na tutela de casos repetitivos do CPC/15 - Victor Barbosa Dutra (2016)
The standardization of legal relationships has challenged Civil Procedural Law in theoretical and practical terms. Over the past decades a number of mechanisms were introduced in Brazil to address the phenomenon: binding precedents, inhibitive precedents, general repercussion as a condition for appealing, representative appealing, and preliminary refusal based on precedents. The new Civil Procedure Code, Law 13,105 of 2015, establishes a new step in systematizing judicial protection of repetitive cases. New institutes were set, such as the incident for judgment of repetitive lawsuits and the incident of assumption of competence and other institutes were improved, for example the extraordinary and special appeals. Beside their specificities, the institutes have a common guideline: to provide legal certainty, uniformity in Courts decisions and therefore procedural promptness on repetitive issues. It happens that, as structured in new Civil Procedure Code, there are doubts on the feasibility of an effective contradictory on the system of repetitive cases what may have a direct impact on legitimacy of decisions from those institutes, since the contradictory is an important element of a democratic process. The research aims to look into the system of repetitive cases, in order to shed light on its dark aspects and thus contribute to the formation of an effective contradictory. The work aims to evaluate what would be the alternatives to enable a democratic and participatory structure in expedients provided by the new Civil Procedure Code to protect the repetitive situations.